Evolution of close-range detection and data acquisition technologies towards automation in construction progress monitoring. (November 2021) - Alaloul, Wesam Salah; Qureshi, Abdul Hannan; Musarat, Muhammad Ali; Saad, Syed
Abstract: Automated construction progress monitoring is the prevalent domain amongst researchers, with much potential for improving digital monitoring technologies and related processes. Effective, efficient, and timely collection of progress data are essential requirements for the success of the construction project. This study investigated and assessed the achievement level of automation attained in construction progress monitoring practices via digital data collection technologies for building construction projects. A mixed review methodology (bibliometric analysis and systematic review) was adopted, and a total of 1560 publications were collected and further screened to 205 articles. Bibliometric analyses were performed considering descriptive statistics, and bibliometric mapping for keywords and monitoring techniques. This study exemplified the framework for the overall conception of the automated construction progress monitoring process, utilising close-range data acquisition and detection technologies. These technologies under construction progress monitoring were analysed for their applications, implementation strategies on building construction projects, and BIM-integrated monitoring. This study also highlighted the current technical challenges, gaps and future opportunities for the modification and evolution of construction progress monitoring processes towards automation. Highlights: Bibliometric and systematic analysis of construction progress monitoring technologies. Keyword analysis and state of the art technique analysis using VOSviewer. General framework expounding automated construction monitoring process. Data acquisition-detection technologies matrix of monitoring tools and techniques. Data acquisition-detection technologies integration with BIM.